Techno-Economic Assessment of Green Hydrogen Production in Australia Using Off-Grid Hybrid Resources of Solar and Wind - Behgol Bagheri; Hiromu Kumagai; Michio Hashimoto; Masakazu Sugiyama (Energies)
This study presents a techno-economic framework for assessing the potential of utilizing hybrid renewable energy sources (wind and solar) to produce green hydrogen, with a specific focus on Australia. The model’s objective is to equip decision-makers in the green hydrogen industry with a reliable methodology to assess the availability of renewable resources for cost-effective hydrogen production. To enhance the credibility of the analysis, the model integrates 10 min on-ground solar and wind data, uses a high-resolution power dispatch simulation, and considers electrolyzer operational thresholds. This study concentrates on five locations in Australia and employs high-frequency resource data to quantify wind and solar availability. A precise simulation of power dispatch for a large off-grid plant has been developed to analyze the PV/wind ratio, element capacities, and cost variables. The results indicate that the locations where wind turbines can produce cost-effective hydrogen are limited due to the high capital investment, which renders wind farms uneconomical for hydrogen production. Our findings show that only one location—Edithburgh, South Australia—under a 50% solar–50% wind scenario, achieves a hydrogen production cost of 10.3 ¢USD/Nm3, which is lower than the 100% solar scenario. In the other four locations, the 100% solar scenario proves to be the most cost-effective for green hydrogen production. This study suggests that precise and comprehensive resource assessment is crucial for developing hydrogen production plants that generate low-cost green hydrogen.